Outlines of the theory of urban agglomerations' self-development - Evgeniy Georgievich Animitsa (Экономика региона, 2012)
This paper discusses new trends in urban centers in Russia. It is noted that the interest of scientists to the problem has increased as urban agglomerations were declared regional areas of priority development. The author gives different interpretations of the content of the concept of «urban agglomeration», which are formulated in the context of different scientific approaches and scientific schools. It is emphasized that the city agglomeration as a special form of reality can be studied in the coordinates of a systemic paradigm. The basic axiomatic features that allow identifying the metropolitan area as a complex system are presented and disclosed. The conclusion was made that a self-developing urban agglomeration is a special type of actively operating territorial unit in which the actors of the local community are able to mobilize local resources by themselves (and, in particular, the human capital) to change the living environment. The paper emphasizes the need to regulate the development of urban agglomerations and gives examples of two basic models of urban agglomerations management.